What role for Chinese FDI in Africa? New survey evidence from Ethiopia and Ghana - Charles Ackah; Alemayehu Geda Fole; Holger Görg; Federico Merchan (Kiel Institute for the World Economy (IfW Kiel), 2024)
Foreign investments bring in not only new employment but also novel technology, managerial skill and know-how, that may also dissipate into the local economy. It is not clear whether this effect differs by the nationality of source countries, in particular between Chinese and non-Chinese firms. Based on a firm level survey on Ethiopia and Ghana, we found that all types of firms are engaged in limited R&D and innovation activity and their transfer to host countries in both countries. There is little difference between Chinese and non-Chinese foreign firms in such technology and managerial skill transfer once controlling for firm size and industry characteristics in the majority of metrices (R&D activities, horizontal & vertical spillover, directly adopting techniques). However, we found for Ghana that Chinese firms have more suppliers but are less likely to transfer technology to them. Chinese firms are more likely to transfer managerial skills than non-Chinese firms in Ghana though not in Ethiopia. Also, there is little evidence that foreign firms transfer technology via horizontal or backward spillovers in either countries. Finally, Chinese firms are much more likely to receive host country policy support than other foreign firms in Ghana but not in Ethiopia.
Keywords: F2; O1; O3; 330; Foreign direct investment; China; Africa; technological transfer; Ethiopia; Ghana